2013
DOI: 10.1007/s00586-012-2645-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity study on the Hungarian versions of the Oswestry Disability Index and the Quebec Back Pain Disability Scale

Abstract: Purpose Patient-reported outcome measurements (PROMs) are widely used in spine care. The development of reliable and valid National versions of spine-related disability questionnaires is strongly recommended from both the clinical and scientific points-of-view. The aims of this study were to adapt and validate the Oswestry Disability Index (ODI) and the Quebec Back Pain Disability Scale (QDS) for use with the Hungarian language. Methods After translating and culturally adapting the ODI and QDS, 133 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 43 publications
(83 reference statements)
5
17
1
3
Order By: Relevance
“…For instance, the MDC 95% value of 7.67 calculated for 14 days indicates that, for a specific patient, a change of more than 8 points is most likely due to true change in the functional disability status of that patient rather than measurement error. This threshold is relativity less than the values reported in most of the previous validation studies of the ODQ (ranging from 9 to 13) [13,21,22,27,32,50,51], and the MODQ (8.8) [36]. The SEM and MDC 95% of the Arabic-MODQ reported in this study suggest the absolute reliability of the questionnaire.…”
Section: Plos Onecontrasting
confidence: 57%
See 1 more Smart Citation
“…For instance, the MDC 95% value of 7.67 calculated for 14 days indicates that, for a specific patient, a change of more than 8 points is most likely due to true change in the functional disability status of that patient rather than measurement error. This threshold is relativity less than the values reported in most of the previous validation studies of the ODQ (ranging from 9 to 13) [13,21,22,27,32,50,51], and the MODQ (8.8) [36]. The SEM and MDC 95% of the Arabic-MODQ reported in this study suggest the absolute reliability of the questionnaire.…”
Section: Plos Onecontrasting
confidence: 57%
“…Cronbach's α = 0.70-0.95 [40] Test-retest ICC > 0.70 [40] SEM � 2.15-6.5 [12,[20][21][22]27,32,34,50] MDC 95% � 6-13.67 [12,13,[20][21][22]27 The MIC was determined by locating the point on the curve nearest to the left-hand corner of the graph. This point is associated with the maximum sensitivity and specificity of the questionnaire and represents a cutoff value to separate patients who have experienced improvements in their condition from those who have not [66].…”
Section: Internal Consistencymentioning
confidence: 99%
“…The MDC 95% found in our study was like that reported in the Croatian version of the ODI (6.0) [37]. The MDC of the ODI-Y was lower than that of the Polish (MDC=10) [41]; German (9.0) [15]; Hungarian (MDC=11) [42] and Chinese (12.8) [43] translations of the ODI. An MDC of 5.5 found in our study implies that below 5.5, the measurement error of the ODI-Y is indistinguishable.…”
Section: Discussionsupporting
confidence: 80%
“…Based on the results above, positive rating for the reliability of the Hungarian RMQ can be given. Authors of the present paper published previously the validation study of the Hungarian ODI [19]. The RMQ and the ODI are the two most widespread and most frequently cited spine related disability questionnaires.…”
Section: Validitymentioning
confidence: 98%
“…Besides the RMQ to be validated, the patients completed the previously validated Hungarian version of the Oswestry Disability Index [18,19] (ODI) as well as the valid Hungarian version of the the WHO Quality of Life-BREF assessment (WHOQoL) [20]. To assess the patients' pain, the 100-mm long Visual Analogue Scale (VAS) was applied [21].…”
Section: Measurement Toolsmentioning
confidence: 99%